Choice Feeding as a Means of Identifying Differences in Nutritional Needs of Broiler Strains Differing in Performance Characteristics - Cerrate, S.; Wang, Z.; Coto, C.; Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2007)
Chickens from two broiler strains known to differ in growth rate and feed conversion (GROWTH) and in high breast meat yield (YIELD) were grown to 10 days of age on a common starter diet and from 11 to 49 days were provided single diets (control), a choice between high energy and high protein diets, or a choice between starter and finisher diets. Overall the YIELD strain had greater body weight, feed intake and breast yield than did GROWTH strain. However, the YIELD strain had better feed conversion only when offered a choice of starter and finisher diets. Birds fed single diets and Starter-Finisher diets had better body weight, feed intake, feed conversion and breast yield than those birds fed Energy-Protein diets. Birds fed both choice feeding systems selected more high energy diets than high protein diets especially during the period of 11 to 22 d of age. The YIELD strain had a preference for the high protein diet and consequently had greater protein intake and average dietary protein content than did the GROWTH strain, while the former ate more energy intake but less energy content than did the latter. Birds given choice of the energy and protein diets had less protein intake and content for all periods, whereas these birds chose less energy intake for the period of 22 to 42 d of age and a higher energy level than did birds fed the other two feeding systems. These data indicate that choice feeding systems can identify differences in performance according to the selected nutritional needs for new strains of broilers.